Macrophage migration inhibitory factor: A key cytokine and therapeutic target in colon cancer. Issue 4 (August 2015) - Gordon-Weeks, A.N.; Lim, S.Y.; Yuzhalin, A.E.; Jones, K.; Muschel, R.
Abstract: Macrophage migration inhibitory factor (MIF) was one of the first cytokines to be discovered, over 40 years ago. Since that time a burgeoning interest has developed in the role that MIF plays in both the regulation of normal physiology and the response to pathology. MIF is a pleotropic cytokine that functions to promote inflammation, drive cellular proliferation, inhibit apoptosis and regulate the migration and activation state of immune cells. These functions are particularly relevant for the development of cancer and it is notable that various solid tumours over express MIF. This includes tumours of the gastrointestinal tract and MIF appears to play a particularly prominent role in the development and progression of colonic adenocarcinoma. Here we review the role that MIF plays in colonic carcinogenesis through the promotion of colonic inflammation, as well as the progression of primary and metastatic colon cancer. The recent development of various antagonists and antibodies that inhibit MIF activity indicates that we may soon be able to classify MIF as a therapeutic target in colon cancer patients.